2019
DOI: 10.1371/journal.pone.0212337
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin associates with the actin cytoskeleton and α-actinin isoforms to influence stimulus dependent morphology changes

Abstract: One response of cells to growth factor stimulus involves changes in morphology driven by the actin cytoskeleton and actin associated proteins which regulate functions such as cell adhesion, motility and in neurons, synaptic plasticity. Previous studies suggest that Huntingtin may be involved in regulating morphology however, there has been limited evidence linking endogenous Huntingtin localization or function with cytoplasmic actin in cells. We found that depletion of Huntingtin in human fibroblasts reduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…We observed that in HD fibroblasts, mHTT formed aggregates that associated with cytoskeletal fibers. Such results are compatible with recently reported observations that HTT can be associated with isoforms of α-actinin that bind actin filaments, and that mHTT localizes specifically to actin stress fibers (Tousley et al 2019 ). Again, treatment with genistein resulted in disappearance of aggregates, and HTT distribution resembling the distribution in healthy cells.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that in HD fibroblasts, mHTT formed aggregates that associated with cytoskeletal fibers. Such results are compatible with recently reported observations that HTT can be associated with isoforms of α-actinin that bind actin filaments, and that mHTT localizes specifically to actin stress fibers (Tousley et al 2019 ). Again, treatment with genistein resulted in disappearance of aggregates, and HTT distribution resembling the distribution in healthy cells.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, mutant Huntingtin may also indirectly affect synaptic function by changing transcription of synaptic genes ( Langfelder et al, 2016 ) or have pleiomorphic effects. For instance, alpha-actinin-2, which is an actin bundling protein, interacts with Huntingtin ( Tousley et al, 2019a ) and also interacts with NMDA 2b in spines ( Wyszynski et al, 1997 ). Alpha-actinin-2 is also transcriptionally downregulated in HD models ( Langfelder et al, 2016 ) which may create instability in spines and impact NMDA 2B receptors distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that during preparation of the fractions in our study homogenization weakened structural integrity to give rise to the altered axon terminal and vesicle morphology we observed. Huntingtin has been implicated in actin morphology directly through interactions with actin ( Angeli et al, 2010 ) and interactions with actin binding proteins such as profilin, cofilin, alpha-actinins ( Culver et al, 2012 ; Shirasaki et al, 2012 ; Tourette et al, 2014 ; Tousley et al, 2019a ) and mutant Huntingtin can exert negative effects through ROCK ( Shao et al, 2008 ), Rac1 ( Tousley et al, 2019b ) and potentially other interacting proteins such as HIP1 and GIT1 ( Harjes and Wanker, 2003 ; Goehler et al, 2004 ). Alternatively, failure of vesicles to bud due to impaired Rab11 dependent trafficking in the presence of mutant Huntingtin ( Li et al, 2009 ) may account for the change in distribution in size of measured particles.…”
Section: Discussionmentioning
confidence: 99%
“…However, immunofluorescence studies have not confirmed those findings. The functional interaction of HTTs with α-actinin isoforms has confirmed by the integrated approach—immunoprecipitation method using exogenously expressed proteins in combination with immunofluorescence and PLA analysis [ 113 ]. The authors suggest that HTT regulates the localization of α-actinin-1 and combines growth factor signaling with actin polymerization and the formation of actin bundles in newly formed adhesion sites.…”
Section: Intracellular Localization Of Huntingtin and Its Associatmentioning
confidence: 99%